Bee Pollen Polysaccharide From Rosa rugosa Thunb. (Rosaceae) Promotes Pancreatic β-Cell Proliferation and Insulin Secretion - Siwen Yang; Yunhe Qu; Jiyu Chen; Si Chen; Lin Sun; Yifa Zhou; Yuying Fan (Frontiers Media S.A., 2021)
Insufficient pancreatic β-cell or insulin-producing β-cell are implicated in all types of diabetes mellitus. Our previous studies showed bee pollen polysaccharide RBPP-P improves insulin resistance in type 2 diabetic mice by inhibiting liver fat deposition. However, its potential of regulating β-cell function and integrity is not fully known. Herein, we observed that β-cell proliferation (n = 10), insulin synthesis (n = 5, p = 0.01684) and insulin incretion (n = 5, p = 0.02115) were intensely activated in MIN6 cells when treatment with RBPP-P. In alloxan-induced diabetic mice, oral administration of RBPP-P (n = 10) effectively decreased the blood glucose (p = 0.0326), drink intake (p < 0.001) and urine (p < 0.001). It directly stimulated phosphorylation of p38 (p = 0.00439), ERK (p = 0.02951) and AKT (p = 0.0072) to maintain the islet function and mass. Thus, our data suggest that RBPP-P is a natural compound to regulate β-cell proliferation and function, indicating it might have therapeutic potential against type 1 diabetes.